Rehabilitation coordinator - managers' experiences of a new function in health care - Catharina Strid; Rosie Benner; Ronja Stefansdotter; Kjerstin Stigmar (BMC, 2024)
Abstract Background Several actions have been taken to improve the sick listing process, patient safety and return to work. One of them is the implementation of the rehabilitation coordinator function, of which the benefits have not yet been fully explored. Neither has the role of the manager, who has significant impact on the implementation and support of a new function. This study aimed to explore how first line managers', who employed a rehabilitation coordinator that had completed a one-year specialized study program, perceived, and experience the function rehabilitation coordinator. Methods This is an interview study using a semi structured interview guide for data collection and thematic analysis was applied to the data. Ten first line managers in health care were interviewed. Results Four themes were identified: The Saviour, A personalized function, Change takes time and Strengthen status and legitimacy. The managers experienced the rehabilitation coordinator as a valuable function who facilitates collaboration in the team and with external stakeholders and perceived them as a much-needed resources, supporting physicians with sick leave issues. The assignment was ambiguous and dependent on the rehabilitation coordinators individual characteristics, which may result in a risk of overload. The managers were engaged in the implementation process, but this required time. They considered it important to strengthen legitimacy for the function which required support and encouragement to take part in specialized education and training. Conclusions The managers experienced the rehabilitation coordinators as playing a crucial role in the return-to-work process. They were willing to support how this new function will improve and develop. The results from this can serve as a guidance for the implementation and support of the function rehabilitation coordinator.